Implementation of Problem Based Learning (PBL) Model Using Maple Software in Solving a Trigonometry Material Problem - Ni’mah, Dewi Nailin; Inganah, Siti; Putri, Octavina Rizky Utami (Mathematics Education Journal, 2024)
This study aims to investigate the implementation and effectiveness of the PBL learning model with Maple Software in solving Trigonometry problems during mathematics lessons. It is descriptive research with a quantitative approach. The participants were 20 tenth-grade students from an vocational school in the second semester of the 2022/2023 academic year. Data were collected through student questionnaires and written tests. The questionnaires assessed student understanding in solving Trigonometry problems with Maple Software, while the tests included 5 questions to evaluate problem-solving skills using the software. The findings indicate that: (1) The PBL model with Maple Software enhances student engagement and effectively solves Trigonometry problems. (2) The PBL model using Maple Software is effective in improving students' problem-solving abilities in Trigonometry.